PERENCANAAN DAN PERANCANGAN AGROWISATA TAMAN UPAKARA DAN USADHA DI DESA BANJAR ANYAR, KEDIRI, TABANAN - I Gede Esa Darma Santika; Putu Gde Ery Suardana; Arya Bagus Mahadwijati Wijaatmaja (Jurnal Anala, 2024)
Planning and design of Upakara and Usada Park Agrotourism aims to create a tourist attraction that focuses on the preservation of upakara and usada plantations and is able to provide education to the public about the importance of protecting the environment, so the focus point in this research is finding interesting themes and design concepts that inspire People's interest in visiting agro-tourism objects and increasing their interest in paying more attention to the environment. The method used in the research is the primary data collection method which is carried out by means of interviews and secondary which is carried out by means of literature study. Then SWOT analysis is used to explore the potential of the research object in order to obtain design concepts and themes. The results of this analysis produce a conclusion on the design theme which is the final goal of this research.